Pengaruh Pendidikan dan Pelatihan (DIKLAT) terhadap Kinerja Pegawai Negeri Sipil pada Kantor Dinas Pendidikan dan Kebudayaan Kabupaten Batang Hari - Etty Siswati; Evi Fauzani; Riado Houlion Sinaga (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of education and training on the performance of civil servants Kantor Dinas Pendidikan dan Kebudayaan Kabupaten Batanghari. This research is a descriptive quantitative research. The sample of this research is 56 people. Based on the results of the partial test (t test). Obtained tcount value for (X) Education and Training (Diklat) is 6.626 and the value of ttable is 1.67303 because the tcount value is greater than the ttable value, it can be concluded that Education and Training (education and training) has a significant effect on the performance of civil servants in Kantor Dinas Pendidikan dan Kebudayaan Kabupaten Batanghari. Based on the results of the R Square determination coefficient of 0.448. So it can be concluded that the percentage effect of the Education and Training (X) variable on the Civil Servant Performance variable on Dinas Pendidikan dan Kebudayaan Kabupaten Batanghari amounting to 0.448 or 44.8% and the remaining 55.2% is influenced by other variables not examined in this study